Women's career management to ensure public justice - Tuğan, Esra Nur; Bilgin, Kamil Ufuk (Akademisyen Yayinevi Kitabevi, 2021)
The purpose of this article is to determine the importance of women's career management to ensure public justice. Because today, women suffer injustice in many different levels and forms all over the world. Unfortunately, in many countries, cultural heritage and traditions are an obstacle to women's health and well-being. In many cultures, women are shown to be less valuable than men and deserve less than men to fundamental rights (such as the right to work and the right to participate in politics), which are directly linked to the quality of life. On the other hand public justice means rebuilding the society in accordance with the principles of equality and inclusion. It requires taking a stand against ideological frameworks, historical legacies, and practices that structure social relations in a way that leads to inequality and thus enable some groups to gain advantage over other marginalized groups. In particular, legal and political equality strengthens public and administrative justice. Consequently, for public justice, opportunities and options should be given to women as well as to those provided to men. For this, it should be ensured that women have sufficient presence in working life. Unless women can balance work-family and work-life due to the traditional roles that society places on women, problems in their career management intimidate them. © Akademisyen Yayinevi Kitabevi 2021. All rights reserved.